Proliferation of Policies on Notarial Supervisory Institutions Based on Justice - Akbar, Adi; Desi Kumalasari; Rizal Alamsyah Hadi Saputra; Yekti Mahardika; Uktamjon Zarifjon ugli Tukhtaev (Journal of Human Rights, Culture and Legal System, 2025)
The current regulatory framework governing notarial responsibility demonstrates normative inconsistency and insufficient grounding in principles of justice, particularly in fraud-related cases; meanwhile, law enforcement practices continue to impose disproportionate legal liability on notaries. This study examines the principle of justice in assessing the legal responsibility of notaries in the execution of authentic deeds, especially in cases involving allegations of malicious intent (mens rea). It further analyzes deficiencies within the existing regulatory framework and proposes a reconstruction of justice-based regulation to ensure balanced legal protection for both notaries and deed signatories. The study adopts a constructivist paradigm with a sociological juridical approach, supported by doctrinal analysis and theoretical review. It employs a descriptive-analytical research design and is grounded in theories of justice, legal system functionality, and progressive law. The findings demonstrate, first, significant normative disharmony between Article 1 Number 6 and Articles 66A and 67 of the Notary Law, particularly concerning overlapping authority between the Notary Supervisory Board and the Notary Honorary Council, which creates institutional ambiguity in supervision and guidance. Second, these regulatory inconsistencies lead to procedural neglect in law enforcement practice and generate legal uncertainty for notaries, particularly during investigation and prosecution processes. Third, the study proposes regulatory reconstruction through amendments to Articles 15, 16, and 17 to strengthen justice-oriented legal protection while maintaining professional accountability. This reconstruction is essential to ensure legal certainty, institutional coherence, professional independence, and balanced protection for all parties.